a) để phương trình có 1 nghiệm bằng 2
\(\Leftrightarrow m2^2-2.2-4m-1=0\Leftrightarrow-5=0\Rightarrow m\in\varnothing\)
b) để phương trình có 2 nghiệm phân biệt \(\Leftrightarrow\left\{{}\begin{matrix}m\ne0\\\Delta'>0\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}m\ne0\\1^2+m\left(4m+1\right)>0\end{matrix}\right.\) \(\Leftrightarrow\left\{{}\begin{matrix}m\ne0\\4m^2+m+1\end{matrix}\right.\) \(\Leftrightarrow m\ne0\)
áp dụng hệ thức vi ét ta có : \(\left\{{}\begin{matrix}x_1+x_2=\dfrac{2}{m}\\x_1x_2=\dfrac{-4m-1}{m}\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}3x_2=\dfrac{2}{m}\\2\left(\dfrac{2}{3m}\right)^2=\dfrac{-4m-1}{m}\end{matrix}\right.\) \(\Rightarrow m\in\varnothing\)
c) ta có : \(x_1< 2< x_2\Leftrightarrow\)\(x_1< mx_1x_2< x_2\Leftrightarrow\dfrac{1}{x_2}< m< \dfrac{1}{x_1}\)
\(\Leftrightarrow\dfrac{m}{1-\sqrt{4m^2+m+1}}< m< \dfrac{m}{1+\sqrt{4m^2+m+1}}\)
\(\Leftrightarrow\dfrac{m}{1-\sqrt{4m^2+m+1}}< m< \dfrac{m}{1+\sqrt{4m^2+m+1}}\)\(\Leftrightarrow m< 0\) vậy \(m< 0\)
d) áp dụng hệ thức vi ét ta có : \(\left\{{}\begin{matrix}x_1+x_2=\dfrac{2}{m}\\x_1x_2=\dfrac{-4m-1}{m}\end{matrix}\right.\)
ta có : \(\dfrac{1}{x_1}+\dfrac{1}{x_2}=\dfrac{x_1+x_2}{x_1x_2}=\dfrac{2}{m}.\left(\dfrac{m}{-4m-1}\right)=2\)
\(\Leftrightarrow\dfrac{2}{-4m-1}=2\Leftrightarrow m=\dfrac{-1}{2}\) vậy \(m=\dfrac{-1}{2}\)